Ageing as a criterium of dynamism in modern Greek insular space – Ionion, Aegean, Crete - Κακλαμάνη Σταματίνα; Duquenne, Marie-Noëlle (Ariadne, 2021)
AGEING in the countryside Greece follows several different paths that hide important disparities. When considering ageing process at local level is not always the result of desertification and therefore it is not always a negative evolution. In the causes contributing to the ageing process – meaning the population receiving weakness – are included both the geomorphologic characteristics of the areas that provoke serious access barriers, and the characteristics of access conditions. In this context, the questions raised and discussed in this paper are: to what extent the above factors – geomorphologic characteristics and accessibility – as discontinuity premises are affecting ageing levels of the insular space, and to what extent ageing is related mainly with problems of isolation particularly affecting the islands? The analysis of ageing is realised at municipality level and concerns 75 Greek islands with a minimum population size of 100 inhabitants. The study of ageing process characteristics is based on data from the last three censuses (1991, 2001, 2011). For the analysis of accessibility, we created eight (8) variables that reflect both the means and conditions of access to the 75 islands under analysis. The Principal Component Analysis and hierarchical classification based on demographic indicators revealed three distinct patterns of ageing in the islands where decisive role played by geomorphologic characteristics, evolution concerning immigration, and developing economic activities that shape the further prospects of the regions. At the island level, the accessibility analysis was based on Hierarchical Classification, highlighting seven (7) groups with distinct accessibility characteristics. According to the results of the analysis the relationship between ageing and accessibility to the mainland is not sufficiently systematic, while the focus in connection with the mainland can work misleading. However there are other important factors such as the size of the island and the variations and/or dissimilarities inside the larger islands. Specifically in the case of smaller islands – besides the above factors – the possibilities and conditions of connection with neighboring larger islands play a determinant role.